The Examination of Life Satisfaction in terms of Emotional Expression, Resilience and Perceived Social Support - Samet Makas; Eyüp Çelik (Istanbul Kültür University, 2022)
This research investigates the mediating effect of resilience and perceived social support in the relationship between life satisfaction and emotional expression. The research data were collected with Satisfaction with Life Scale, Resilience Scale, The Emotional Expression Questionnaire, and Multidimensional Scale of Perceived Social Support. It was tested using a multiple serial mediation model in accordance with the hypothesis of the research, whether mediation role of resilience and perceived social support in the relationship between life satisfaction and emotional expression. As a result of research, it has been realized that life satisfaction has a significant positive relationship with emotional expression, resilience, and perceived social support. Furthermore, the result of mediation analysis showed that resilience and perceived social support have a mediation role in the relationship between life satisfaction and emotional expression.